Biology and Management of Poison Ivy (Toxicodendron radicans) in the Home Landscape - Yuvraj Khamare; Chris Marble (EDIS)
Poison ivy is an allergenic plant of the cashew family native to North America. Poison ivy, poison oak, and poison sumac all grow in Florida and contain the oily resin called urushiol. This new 4-page publication of the UF/IFAS Environmental Horticulture Department was written to aid landowners, gardeners, horticulturalists, and pest management professionals in identification and management of poison ivy in residential and commercial landscapes. Written by Yuvraj Khamare and Chris Marble.